(untitled) (Research, Society and Development, 2024)
Peripheral arterial occlusive disease (PAOD) or peripheral arterial disease (PAD) is a pathology that results from the concentration of atheromatous plaques in the arteries, especially in the lower limbs. The disease is influenced by numerous risk factors, such as diabetes mellitus, atherosclerosis, arterial hypertension, chronic kidney disease and smoking. The objective of this study is to analyze the influence of risk factors on the clinical and surgical outcome of peripheral arterial occlusive disease. To carry out the study, the research methods epidemiological analysis and literature review were combined. Regarding the literature review, 25 articles were selected, in English, Portuguese and Spanish, using the PubMed, Scielo, LILACS and UptoDate databases. The research was conducted based on the descriptors “peripheral arterial disease”, “diabetes”, “atherosclerosis”, “smoking”, “chronic kidney disease”, “prognosis” and “hypertension”. In the epidemiological analysis, the medical records of 333 patients with PAOD admitted to the Vascular Surgery Department of the Federação Beneficente Hospital Cirurgia in Aracaju, Sergipe, and undergoing treatment at the institution were analyzed. Based on the correlation between the results found, the influence of the risk factors studied on the development and outcome of the disease became clear, as well as on the viable treatment possibilities according to the comorbidity analyzed. Furthermore, it was evident that greater primary control of risk factors can prevent greater future complications in the course of the disease.